2010
DOI: 10.1021/ja1061196
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene-Catalyzed Conjugate Additions of Alcohols

Abstract: An efficient intermolecular conjugate addition of alcohols to activated alkenes catalyzed by N-heterocyclic carbenes has been developed. With 5 mol % of the free carbene derived from IMes•HCl, unsaturated ketones and esters are competent substrates and a variety of primary and secondary alcohols can be employed as the nucleophile. No oligomerization is observed under these mild conditions for effective hydroalkoxylation. In addition to reactions with activated alkenes, IMes catalyzes the formation of vinyl eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(78 citation statements)
references
References 45 publications
2
72
1
3
Order By: Relevance
“…Confirming our initial hypothesis, we found that strong Brønsted base NHCs, such as N,N-dialkylimidazolium-generated NHCs, neither catalysed nor generated appreciable conversion for this reaction. This result is in sharp contrast to previous reports that used NHCs as Brønsted bases for both oxy-and carbo-Micheal addition reactions 45,46 . Those reports primarily used N-alkyl imidazolium-derived NHCs because they are strongly basic.…”
Section: Analysis Of Nhc-catalysed Michael Addition Reactionscontrasting
confidence: 99%
See 1 more Smart Citation
“…Confirming our initial hypothesis, we found that strong Brønsted base NHCs, such as N,N-dialkylimidazolium-generated NHCs, neither catalysed nor generated appreciable conversion for this reaction. This result is in sharp contrast to previous reports that used NHCs as Brønsted bases for both oxy-and carbo-Micheal addition reactions 45,46 . Those reports primarily used N-alkyl imidazolium-derived NHCs because they are strongly basic.…”
Section: Analysis Of Nhc-catalysed Michael Addition Reactionscontrasting
confidence: 99%
“…A recent study on NHCcatalysed oxy-Michael addition showed that facial discrimination was poor with popular chiral-NHC scaffolds; only 11% enantioselectivity was achieved for an intramolecular addition reaction, possibly as a result of a loosely stacked catalyst/substrate ion pair (Fig. 2b) 45 . In a separate report on carbo-Michael addition, strongly basic NHCs showed excellent catalytic activity.…”
Section: Analysis Of Nhc-catalysed Michael Addition Reactionsmentioning
confidence: 99%
“…5061 These unique Lewis bases have been used to generate acyl anion, 6276 homoenolate, 7794 and enolate equivalents, 41,95105 as well as promote hydroacylation 106111 and an exciting variety of non– Umpolung processes. 112115 These carbene-catalyzed processes have been used to access numerous challenging compound classes with high levels of diastereo- and enantioselectivities. With all of the different reaction manifolds accessed through carbene catalysis, it is interesting to note that before our 2012 report, there had been no previous examples in the literature of NHCs facilitating a DKR.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, catalysis by N-heterocyclic carbenes (NHCs) has received considerable attention, [6] and we have recently reported the serendipitous discovery of the excellent organocatalytic activity of N,N-diaryl-1,3-imidazol(in)-2-ylidenes in intramolecular Michael additions of 1,3-dicarbonyl compounds, and its application to the stereoselective synthesis of spiro compounds (Scheme 1). [7] Herein, we report our studies on the scope of the NHC-catalyzed Michael addition [8] of 1,3-dicarbonyl derivatives and related compounds, some applications to stereoselective organocatalytic domino carbocyclization reactions, and the results of early mechanistic investigations.…”
Section: Introductionmentioning
confidence: 99%